Performance Based Capitation Settings in the National Health Insurance Program for Primary Healthcare Facilities - Yulia Susanti; Khairani (Dinasti Research, 2025)
The National Health Insurance Program by the Health Social Security Administration Agency aims to provide access to quality, safe, and affordable health services. A capitation payment system is implemented for Primary Healthcare Facilities based on the number of registered participants, but this system faces obstacles in encouraging service quality improvement. To address this, Performance-Based Capitation was developed with key indicators such as contact numbers, non-specialist referral ratios, and controlled Prolanis participant ratios. This study uses normative juridical methods to analyze the regulations, implementation, and challenges of Performance-Based Capitation in National Health Insurance. The data was analyzed qualitatively through a study of laws and regulations, scientific literature, and related reports. The results of the study show that the implementation of Performance-Based Capitation is effective in increasing the utilization of Primary Healthcare Facilities, reducing the referral rate to an advanced level, and improving the management of chronic diseases. However, there are obstacles in the form of limited infrastructure, resource inequality, and lack of coordination between stakeholders. To increase the success of Performance-Based Capitation, it is necessary to strengthen regulations, increase the capacity of human resources, utilize information technology, and provide performance-based incentives.